What Drives the Purchase of MSME Products? The Role of Social Media Marketing in Emerging Markets - Auliandri, Tuwanku Aria; Setyawan, Andhy; Djayapranata, Grace Felicia; Lestari, Yetty Dwi; Kartika, Nurullaily; Barinta, Dunga Dwi; Khaira, Nurul; Musthofa, Zainul (International Journal of Entrepreneurship, Business and Creative Economy, 2025)
This research aims to identify external factors that influence purchase intention in the use of social media for Micro, Small and Medium Enterprises (MSMEs) in emerging markets, focusing on how user attitudes towards social media marketing strategies can influence consumer intentions to purchase MSME products. Quantitative approach is used with an explanatory research type, by collecting survey data from 413 social media users who engage with MSME products in East Java, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to determine the significance of each factor. The results show that interactivity, informativeness, word of mouth (WOM), personalization, trendiness, entertainment, usefulness, and flow experience significantly positively affect Purchase Intention. Conversely, Irritation has a negative effect. User attitude towards social media is an important mediating factor that strengthens the influence of these variables on purchase intention, suggesting that positive experiences on social media can increase consumers' likelihood of purchase. Limitation of this study is conducted only within specific geographical area (East Java), which may affect the generalizability of the results. Further research can be conducted with a broader sample to validate these findings in other regions and markets. This research provides insights into the role of social media attributes and user experience in driving Purchase Intention in the MSME sector in emerging markets. It highlights the importance of positive user attitudes, thus filling the research gap regarding the impact of social media on consumer behavior in the context of MSMEs.